Distribution of melanopsin positive neurons in pigmented and albino mice: Evidence for melanopsin interneurons in the mouse retina - Francisco Javier Valiente-Soriano; Diego eGarcía-Ayuso; Arturo eOrtín-Martínez; Manuel eJiménez-López; Caridad eGalindo-Romero; María Paz Villegas-Pérez; Marta eAgudo-Barriuso; Anthony Alexander Vugler; Manuel eVidal-Sanz (Frontiers Media S.A., 2014)
Here we have studied the population of intrinsically photosensitive retinal ganglion cells (ipRGCs) in adult pigmented and albino mice. Our data show that although pigmented (C57Bl/6) and albino (Swiss) mice have a similar total number of ipRGCs, their distribution is slightly different: while in pigmented mice ipRGCs are more abundant in the temporal retina, in albinos the ipRGCs are more abundant in superior retina. In both strains, ipRGCs are located in the retinal periphery, in the areas of lower Brn3a+RGC density. Both strains also contain displaced ipRGCs (d-ipRGCs) in the inner nuclear layer that account for 14% of total ipRGCs in pigmented mice and 5% in albinos. Tracing from both superior colliculli shows that 98% (pigmented) and 97% (albino) of the total ipRGCs, become retrogradely labelled, while double immunodetection of melanopsin and Brn3a confirm that few ipRGCs express this transcription factor in mice. Rather surprisingly, application of a retrograde tracer to the optic nerve labels all ipRGCs, except for a sub-population of the d-ipRGCs (14% in pigmented and 28% in albino, respectively) and melanopsin positive cells residing in the ciliary marginal zone (CMZ) of the retina. In the CMZ, between 20% (pigmented) and 24% (albino) of the melanopsin positive cells are unlabelled by the tracer and we suggest that this may be because they fail to send an axon into the optic nerve. As such, this study provides the first evidence for a population of melanopsin interneurons in the mammalian retina.